Investigation of congestive heart failure in beef cattle in a feedyard at a moderate altitude in western Nebraska. (July 2019) - Moxley, Rodney A.; Smith, David R.; Grotelueschen, Dale M.; Edwards, Tom; Steffen, David J.
Right-sided congestive heart failure (brisket disease) commonly occurs in cattle raised at elevations >2, 500–3, 500 m. We investigated clinical cases resembling brisket disease at a western Nebraska feedyard at a moderate altitude (1, 369 m). Over a 15-mo period (2009–2010), we examined 17 cases (16 steers and 1 heifer), all purebred Angus. All animals had clinical right-sided heart failure: brisket and ventral abdominal edema, and severe chronic passive congestion of the liver. Gross examination confirmed right ventricular hypertrophy (left ventricle plus septum: right ventricle weight ratio mean: 1.33 vs. 2.8–4.0 reference interval). Microscopically, all 17 cases had interstitial fibrosis (mean score: 2.4 ± 0.8) and 6 had replacement fibrosis of the right ventricle, whereas 14 had interstitial fibrosis (mean score: 1.2 ± 0.2) and 0 had replacement fibrosis of the left ventricle. Lesions of arteriosclerosis were seen in 9 of 16 cases in 51 of 571 (8.9%) right ventricular coronary arteries, and in 10 of 16 cases in 52 of 366 (14.2%) left ventricular coronary arteries. The probability of coronary arteriosclerosis was greater in papillary ventricular muscle (OR = 11.3; p < 0.0001), left ventricle (OR = 4.8; p < 0.0001), and larger arteries (OR = 1.01; p < 0.0001). Pulmonary arteries and arterioles had lesions compatible with hypoxia-induced pulmonary hypertension. We hypothesize that moderate hypobaric conditions significantly contributed to disease in cattle genetically predisposed to hypoxia-induced pulmonary hypertension. Adiposity, coronary arteriosclerosis, and left ventricular fibrosis may have contributed to the condition; however, the cattle died prior to development of advanced obesity.